2015
DOI: 10.2188/jea.je20140093
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Long-Chain n-3 and n-6 Polyunsaturated Fatty Acid Profiles and Glomerular Filtration Rate Assessed by Serum Creatinine and Cystatin C Levels in Japanese Community-Dwellers

Abstract: BackgroundPlasma concentration of n-3 polyunsaturated fatty acids (PUFAs) has been reported to be associated with renal function in Western populations. However, few studies have investigated the association between serum long-chain n-3 and n-6 PUFA profiles and renal function in a Japanese population with high marine-derived long-chain n-3 PUFA intake.MethodsA cross-sectional study was performed in 549 Japanese rural community-dwellers aged 40 to 64 years. In adjusted analysis of covariance, we assessed the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The demethylating effect of DHA observed by us in Caco2 cells confirms the finding of our previous study obtained in the same colorectal cancer cells [34]. The rationale for using 100 μM concentration as the selected dose was that it is below or within the reported circulating fatty acid range [42]. The rationale for using a 24-h stimulation was that epigenetic responses to fatty acids and lipoproteins were observed in macrophages and cancerous cells cultured in vitro [4246].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The demethylating effect of DHA observed by us in Caco2 cells confirms the finding of our previous study obtained in the same colorectal cancer cells [34]. The rationale for using 100 μM concentration as the selected dose was that it is below or within the reported circulating fatty acid range [42]. The rationale for using a 24-h stimulation was that epigenetic responses to fatty acids and lipoproteins were observed in macrophages and cancerous cells cultured in vitro [4246].…”
Section: Discussionsupporting
confidence: 84%
“…The rationale for using 100 μM concentration as the selected dose was that it is below or within the reported circulating fatty acid range [42]. The rationale for using a 24-h stimulation was that epigenetic responses to fatty acids and lipoproteins were observed in macrophages and cancerous cells cultured in vitro [4246]. Previous studies reported that PUFA supplementation, namely DHA, at 100 μM for 24 h, may induce cytotoxic effects to cancer cells, altering the normal cellular metabolic pathways and making a possible bias to the final effects/results [47].…”
Section: Discussionmentioning
confidence: 99%
“…Docosahexaenoic acid is an omega-3 essential fatty acid mostly found in fish oil and higher circulating levels have been related to lower inflammatory biomarkers and lower incidence of diabetes [ 23 ], overall mortality [ 24 , 25 ], CVD [ 26 28 ] and atrial fibrillation [ 29 ]. In dialysis patients, docosahexaenoic acid has been shown to be low and associated to increased risk of cardiovascular events [ 30 ] and higher levels of docosahexaenoic acid have been positively related to eGFR in the general population [ 31 ]. Supplementation of omega-3 fatty acid is still polemic [ 32 ] but has been shown to have some beneficial effects in IgA nephropathy [ 33 35 ], on eGFR decline after myocardial infarction [ 36 ], and on blood pressure in CKD patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…were carried out for 24 h using FAs in the 0-200 mM concentration range. These concentrations are below or within the reported circulating FA range-see, for example, Higashiyama et al 26 The rationale for using a 24-hour stimulation is that epigenetic responses to lipoproteins were observed in THP-1 macrophages, a differentiated version of THP-1 monocytes. 12,13 In accordance with a similar study of AA-stimulated THP-1 cells, where cell proliferation was scored based on 3 H-thymidine incorporation, 27 FAs did not affect cell proliferation as assessed by cell counting.…”
Section: Effects Of the Pure Aa And Oa On Global Dna Methylation In Cmentioning
confidence: 92%